A high-content screening platform with fluorescent chemical probes for the discovery of first-in-class therapeutics. Issue 47 (11th May 2016) - Jo, Ala; Jung, Jinjoo; Kim, Eunha; Park, Seung Bum
Abstract : Phenotypic screening as a promising approach to discover novel first-in-class therapeutic agents. Abstract : Phenotypic screening has emerged as a promising approach to discover novel first-in-class therapeutic agents. Rapid advances in phenotypic screening systems facilitate a high-throughput unbiased evaluation of compound libraries. However, limited sets of phenotypic changes are utilized in high-content screening, which require extensive genetic engineering. Therefore, it is critical to develop new chemical probes that can reflect phenotypic changes in any type of cells, especially primary cells, tissues, and organisms. Herein, we introduce our continuous efforts in the development of fluorescent bioprobes and their application to phenotypic screening. In addition, we emphasize the importance of the phenotype-based approach in conjunction with target identification at an early stage of research to accelerate the discovery of therapeutics with new modes of action.